Integral clinical and neuroimaging criteria for the prognosis of spontaneous supratentorial intracerebral hemorrhage acute period outcome - Kuznietsov, A. A. (Zaporozhye Medical Journal, 2018)
The purpose of this study was to develop integrated clinical and neuroimaging criteria for the prediction of spontaneous supratentorial intracerebral hemorrhage (SSICH) acute period outcome. Materials and methods. Complex clinical and neuroimaging study was conducted in 105 patients (56 men and 49 women, mean age 63.6 ± 1.2 years) with SSICH in acute period of the disease receiving conservative therapy. The examination included computer tomography of the brain and clinical assessment using National Institute of Health Stroke Scale (NIHSS), Glasgow Coma Scale (GCS). The disability level was detected in accordance with the modified Rankine Scale (mRS) on the 21st day of the disease. Results. Lethal outcome (21.9 %), unfavourable functional outcome in the form of 4–5 points in accordance with the mRS (33.4 %) and favourable functional outcome in the form of ≤3 points in accordance with the aforementioned scale on the 21st day of SSICH (45.7 %) were registered. The mathematical model has been elaborated for the prediction of lethal outcome of SSICH acute period, which takes into account the initial level of neurological deficit in accordance with NIHSS, the lesion volume and septum pellucidum displacement at the onset of the disease (AUC = 0.91 (0.84–0.96), P < 0.01). The mathematical model has been elaborated for the prediction of functional outcome of SSICH acute period, which takes into account the patient’s age, the level of neurological deficit in accordance with NIHSS, the lesion volume at the onset of the disease (AUC = 0.89 (0.80–0.95), P < 0.01). Conclusions. Integral clinical and neuroimaging predictors of the lethal outcome of SSICH acute period (Se = 91.3 %; Sp = 82.9 %; accuracy of prediction = 85.7 %) and mRS score ≤3 on the 21st day of the disease (Se = 85.4 %; Sp = 82.4 %; accuracy of prediction = 80.5 %) were determined.